PENGARUH GREEN ACCOUNTING, KEPEMILIKAN SAHAM PUBLIK, DAN PROFITABILITAS TERHADAP PENGUNGKAPAN CSR SEKTOR PERTAMBANGAN DI PERIODE BEI 2021-2024 - Anita Maryanti Sari; Ade Manggala Hardianto; Muhammad Panca Prana Mustaqim Sinaga; Ce Gunawan; Yuli Novitasari (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This research is motivated by the limited consistency of CSR disclosure among mining companies, which have a significant impact on environmental and social aspects. The study aims to analyze the influence of green accounting, public share ownership, and profitability on CSR disclosure. The research employs a quantitative method with a descriptive-associative approach. Data were analyzed using panel data regression with a Fixed Effect Model (FEM), determined based on the Chow and Hausman tests. The results show that, partially, green accounting, public share ownership, and profitability do not have a significant effect on CSR disclosure. However, simultaneously, these three variables influence CSR. These findings indicate that individually, the variables have not yet become determining factors in CSR disclosure practices, but collectively they still contribute to the company's non-financial reporting.